The historical decline of tobacco smoking among United States physicians: 1949–1984 - Derek R Smith (Tobacco Induced Diseases, 2008)
Background Tobacco use became an ingrained habit in the United States (US) following the First World War and a large proportion of physicians, similar to the general population, were smokers. The period from 1949 to 1984 was a pivotal era of change however, as the medical profession, like the society it served, became increasingly aware of the dangers that tobacco incurred for health.